Evaluation of advanced lines of Brassica carinata for drought response (Journal of Oilseed Brassica, 2026)
Ethiopean mustard (Brassica carinata) is one of the six commercially important Brassica species and is considered to be tolerant to drought, diseases and insect-pest so better adapted to problematic areas. Drought is an abiotic stress which hampers the yield and productivity of crop. The present investigation aimed at evaluation of advanced lines of Brassica carinata for drought response. The experiment was conducted at G.B. Pant University of Agriculture and Technology, Pantnagar, India. The experimental material consisted of thirty seven advanced lines of B. carinata along with three checks, two of B. carinata cultivar Pusa Swarnim and Kiran and one of B. juncea cultivar Giriraj. Relative leaf water content, Water saturation deficit and electrolyte leakage were taken as indicators of drought response. ANOVA revealed significant differences for all three drought related parameters among genotypes. Kiran showed excellent capacity to manage the stress condition through high relative leaf water content, low water saturation deficit and moderate electrolyte leakage. 30 lines showed significant better response in relation to electrolyte leakage than Kiran. Indian mustard check Giriraj showed poorest response towards the stress condition. For other parameters lines showed intermediate response towards drought. The genotypes identified better for stress condition after confirmation can be further used either as one of the parent for hybridization programme targeted for stress condition. Therefore, with better insight of exploitable variability maximum gain in form of potential cultivar can be achieved to meet out future challenges